2010
DOI: 10.1016/j.mri.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

BOLD responses to trigeminal nerve stimulation

Abstract: The current study investigates a new model of barrel cortex activation using stimulation of the infraorbital branch of the trigeminal nerve. A robust and reproducible activation of the rat barrel cortex was obtained following trigeminal nerve stimulation. Blood oxygen leveldependent (BOLD) effects were obtained in the primary somatosensory barrel cortex (S1BF), the secondary somatosensory cortex (S2) and the motor cortex. These cortical areas were reached from afferent pathways from the trigeminal ganglion, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 51 publications
(73 reference statements)
2
31
0
4
Order By: Relevance
“…induced robust and intense BOLD activation in the barrel cortex for a well-defined range of stimulus current intensities and stimulus frequencies using a short stimulation paradigm (Just et al, 2010). Prolonged TGN stimulation demonstrated that BOLD activation takes place similarly in the primary somatosensory barrel field cortex although the number of active pixels was only slightly decreased compared to short stimulation.…”
Section: Tablementioning
confidence: 94%
See 4 more Smart Citations
“…induced robust and intense BOLD activation in the barrel cortex for a well-defined range of stimulus current intensities and stimulus frequencies using a short stimulation paradigm (Just et al, 2010). Prolonged TGN stimulation demonstrated that BOLD activation takes place similarly in the primary somatosensory barrel field cortex although the number of active pixels was only slightly decreased compared to short stimulation.…”
Section: Tablementioning
confidence: 94%
“…The cathode was inserted in the hiatus infraorbitalis as described in Nielsen and Lauritzen (2001) and the anode was inserted in the masticatory muscles. Electrical stimulation of one trigeminal nerve was performed by delivering square pulses using an external stimulator (WPI, Stevenage, UK) (Just et al, 2010). Previous investigations using TGN electrical stimulations demonstrated that the BOLD response was optimized for stimulation currents in the range 1-3 mA and for a stimulation frequency of 1 Hz (Just et al, 2010).…”
Section: Trigeminal Nerve Stimulationmentioning
confidence: 99%
See 3 more Smart Citations